Investigation of distress of a reinforced earth wall in Hong Kong. Issue 3 (12th April 2018) - Lo, Dominic O K; Cunningham, Jane; Burland, John B
Abstract : During an intense rainstorm on 22 May 2013, severe distress occurred at a reinforced earth wall in Hong Kong. The wall was under construction and nearing completion at the time of the incident. The distress involved the dislodgement of 78 facing panels, a total soil loss of about 1300 m 3 and a disturbed groundmass of some 5500 m 3 . The distress occurred at three localised areas along the wall, with the formation of a sinkhole within the backfilled soil mass, referred to as the backyard of the wall. The incident resulted in significant soil deposition within the surface drainage system, flooding and debris overspill onto the road carriageway below, and it caused havoc to the local community. Subsequent to the incident, a detailed investigation was conducted to establish the probable causes and mechanism of the incident. This paper highlights some salient points of the investigation, the key findings and the lessons learnt from the incident.